Firm Size, Ownership Structure, and Firm Value on Sustainability Expenditures in Indonesian Palm Oil Firms: A Moderated Mediation - Martinus Robert Hutauruk; Firmansyah Firmansyah; Meutia Layli; Astrid Faradisty; Kusumaningdiah Retno Setiorini (Jurnal Dinamika Akuntansi dan Bisnis, 2026)
The palm oil sector is vital to Indonesia’s economy but faces increasing scrutiny over deforestation, greenhouse gas emissions, and social conflicts. Growing global ESG pressures have driven firms to expand sustainability expenditures, yet the roles of firm size and ownership structure in shaping these investments remain underexplored. This study develops a moderated mediation model integrating firm characteristics, governance, and sustainability spending. Using panel data from 276 firm-year observations (2019–2024) and Hayes’s PROCESS macro, the analysis examines direct, indirect, and moderating effects. Firm size increases sustainability spending; firm value weakens relationships